How Inpatient Rehabilitation Transform ed a Geriatric Male with Severe Frailty and Depression: A Case Report - Regina E Gusti; Irma R Defi; Istingadah Desiana; Aditya A Muchtar (Journal of Medicine and Health, 2026)
Frailty, sarcopenia, and depression are interconnected geriatric syndromes that worsen functional decline and quality of life. Previous literature has mainly focused on single-domain interventions, while reports on multidomain inpatient rehabilitation in severely frail elderly patients with recurrent pneumonia remain scarce. This case report aimed to evaluate the benefits of a multidomain inpatient rehabilitation program on physical and mental recovery in a geriatric patient with severe frailty, depression, and recurrent pneumonia. This case report describes a 72-year-old male with de Morton Mobility Index (DEMMI) 0, Strength, Assistance with walking, Rising from a chair, Climbing stairs, Falls (SARC-F) 8, Clinical Frailty Scale (CFS) 7, and Geriatric Depression Scale (GDS) 11 who underwent twice-daily cardiopulmonary endurance training using arm ergometer cycling for 20 minutes (0 watts, 30–40 RPM) with gradual increments, combined with Cognitive Behavioral Therapy (CBT) and progressive mobilization exercises. After two weeks, the patient showed meaningful improvements: DEMMI increased to 8, GDS decreased to 8, SARC-F improved, and bronchopneumonia resolved, while sarcopenia remained stable. Comprehensive rehabilitation combining aerobic exercise, CBT, and mobilization exercises effectively improves mobility, mood, and frailty in geriatric patients. In conclusion, multidisciplinary approaches are important for managing complex geriatric conditions.